An Integrated Public Accountability Model: Lessons from the Pandemic - Nurkholis Nurkholis (Jurnal Ilmiah Akuntansi, 2024)
The Integrated Public Accountability Model proposes a comprehensive framework for enhancing accountability in public organizations, emphasizing both technical and non-technical aspects as foundational pillars. This model advocates for a strategic approach where accounting serves as the primary vehicle for delivering performance information, supported by the pillars of institutional capacity, robust governance, spirituality/religiosity, and local customs. By focusing on these dimensions, the model aims to address the diverse informational needs of stakeholders, ensuring that public organizations deliver high-quality economic and social performance data. The potential impact of this research extends beyond traditional accountability frameworks by highlighting the necessity for an integrated approach during uncertain times, such as pandemics, where typical governance structures are disrupted. Future research should explore the empirical applicability of this model across different cultural and institutional contexts to validate its effectiveness in real-world scenarios. Additionally, studies should consider the dynamic interaction between these pillars to understand how they collectively contribute to enhancing accountability in public sectors. By pursuing these avenues, further research can refine the model's components and their interrelations, potentially establishing a new paradigm for public accountability that is both inclusive and adaptive to various governance challenges.